APPLICATION OF THE PRECAUTIONARY PRINCIPLE IN THE RECORDING OF THE DEED OF NOTARIAL SALE AND PURCHASE BINDING AGREEMENT ON LAND AT THE LAND OFFICE - Agung Iriantoro (NOTARIIL Jurnal Kenotariatan, 2024)
An agreement is an agreement of both parties to do a deed. Agreements are very often used in everyday life, both underhand and notary agreements. In the content of the agreement the parties make in accordance with the principle of freedom of contract. Agreements under hand often have problems between parties because the agreement is not strong binding. For this reason, the role of the Notary Public is needed in making a notarial agreement deed so that the parties can achieve their respective goals and it is safe if one day there is a party who defaults, the notarial agreement deed can be used as valid evidence. The principle of prudence into the deed of Notarial Sale and Purchase Binding Agreement on registered land to be recorded at the Land Office. Using normative methods with a statutory approach and a legal concept approach. The results of this study show that the Notarial Sale and Purchase Binding Agreement Arrangement on registered land registered at the Land Office can only be carried out against the Notarial Sale and Purchase Binding Agreement that has been paid off. The formulation of the precautionary principle into the Notarial Sale and Purchase Binding Agreement deed on registered land that will be registered at the Land Office can be seen in the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 16 of 2021, which can be done using analogous arguments by Notaries in applying the precautionary principle to the preparation of the Sale and Purchase Binding Agreement Deed.